Conflict Talks between Couples in Modern Family Based on Speech Act Theory - Yi, Lin (Journal of English Language Teaching and Applied Linguistics, 2022)
Conflict talk, also known as controversial discourse, is a kind of confrontational communicative behavior arising from differences between two or more parties in views, interests and desires. This study regards conflict talk as a kind of compound speech act. Based on the observation and interpretation of the linguistic data, this study mainly collects the conflict talks between couples in the American sitcom Modern Family and adopts both qualitative and quantitative approaches to analyze the pragmatic characteristics and pragmatic functions of the conflict talks between American couples from the perspective of locutionary act, illocutionary act, perlocutionary effect on the theoretical basis of the speech act theory. The research verifies the feasibility of speech act theory in analyzing conflict talks between couples in Modern Family. It helps us to understand conflict talks between couples from the point of pragmatics better.